Pravice narodov kot posebna oblika človekovih pravic - Peteani, Loredana (Bogoslovni vestnik, 2003)
The role of a nation and its culture is to help man developing his personality. Therefore nations do not only have to be protected, but their development and culture have to be fostered as well. The nation creates and furthers culture, safeguards national traditions and transmits them to new generations in its own language. The nation, however, is not the final vehicle of culture, this is man as a person. It has been tried to base and justify the rights of nations at this level. At the time of global integrations it is very important to emphasize equal respect for all national cultures because every culture expresses the mysteries of human existence. This is also the only path to more human relations between nations, which will enable every nation and its members to collaborate on an equal level in building a better future.
Keywords: dokumenti OZN; dostojanstvo človeške osebe; družbeni nauk Cerkve; narodnostno vprašanje; pravice narodov